Design, Fabrication, and Testing of Small Wind Pump - QUIPO, JUNE (UIR PRESS, 2024)
The demand for energy used to pump water for irrigation has been increasing, resulting in the need for alternative renewable energy sources to reduce costs. A study was conducted to develop a small wind pump that could be used to irrigate crops. The wind pump's efficiency, discharge, and actual power generated were evaluated, and regression analysis and the coefficient of determination were used to determine the goodness of fit. Results showed that the wind pump required a minimum wind speed of 0.3 m/s produced a discharge of 0.95 L/min, while a 4.13m/s wind speed produced a water discharge of 5.45 L/min. The efficiency of the wind pump was measured using the regression equation E= - 04075(ws)² - 0.6375(ws) + 14.36, where R² = 0.6201, resulting in a maximum efficiency of 20.56% and a minimum of 5.57%. This indicates that the wind pump was efficient at low wind speeds due to the dynamic stress of the pump lift rod and a mismatch between the rotor and pump characteristics. Lastly, the net benefit of Php 25,083.61 per year was derived, with a return on investment of 33.86%, which will be paid back in 1.26 months.